1998
DOI: 10.1212/wnl.50.5.1222
|View full text |Cite
|
Sign up to set email alerts
|

Metrifonate benefits cognitive, behavioral, and global function in patients with Alzheimer's disease

Abstract: Metrifonate was safe and well-tolerated. It enhanced not only the cognitive and global function, but also the behavioral function of patients diagnosed with mild to moderate AD. Therefore, metrifonate appears to be useful in the symptomatic treatment of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
150
2
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(166 citation statements)
references
References 15 publications
11
150
2
3
Order By: Relevance
“…Kaufer [22•] reported beneficial effects of metrifonate in AD patients on the NPI total score, aberrant motor behavior, and in symptoms of depression, apathy and hallucinations when compared with placebo in a 26-week trial. In a study by Morris et al [23] metrifonate was associated with improvements in behavioral and global functioning as well as cognitive functioning in mildmoderate AD patients over a 36-week period when compared with placebo. Cummings et al [24] and Raskind et al [25] reported similar results in mild-moderate AD patients over a 6-month period as measured by the NPI.…”
Section: Metrifonate In Alzheimer's Diseasementioning
confidence: 98%
“…Kaufer [22•] reported beneficial effects of metrifonate in AD patients on the NPI total score, aberrant motor behavior, and in symptoms of depression, apathy and hallucinations when compared with placebo in a 26-week trial. In a study by Morris et al [23] metrifonate was associated with improvements in behavioral and global functioning as well as cognitive functioning in mildmoderate AD patients over a 36-week period when compared with placebo. Cummings et al [24] and Raskind et al [25] reported similar results in mild-moderate AD patients over a 6-month period as measured by the NPI.…”
Section: Metrifonate In Alzheimer's Diseasementioning
confidence: 98%
“…In a 26-week, doubleblind study of metrifonate treatment in patients with mild to moderate AD, the NPI was used to measure behavioral outcomes. 31 Metrifonate treatment was associated with significantly less decline in neuropsychiatric disturbances compared with placebo (p < .05). 31 A recent meta-analysis of clinical studies assessing neuropsychiatric outcomes with the NPI in patients with mild to moderate AD reported modest benefits of the ChE inhibitors tacrine, donepezil, galantamine, and metrifonate for behavioral symptoms.…”
Section: Cholinesterase Inhibitors and Behavioral Symptoms Of Alzheimmentioning
confidence: 93%
“…31 Metrifonate treatment was associated with significantly less decline in neuropsychiatric disturbances compared with placebo (p < .05). 31 A recent meta-analysis of clinical studies assessing neuropsychiatric outcomes with the NPI in patients with mild to moderate AD reported modest benefits of the ChE inhibitors tacrine, donepezil, galantamine, and metrifonate for behavioral symptoms. 40 However, interpretation of these results is limited by the low incidence of behavioral problems and the use of psychoactive medications in this patient cohort.…”
Section: Cholinesterase Inhibitors and Behavioral Symptoms Of Alzheimmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition to changes in cognition, cholinesterase inhibitors also have a beneficial effect on behaviour, reducing apathy, visual hallucinations and purposeless activity such as pacing. 5,6 Cognitive and behavioural abnormalities in AD produce distress in caregivers, and improvement in either of these domains ameliorates caregiver burden. 5 Cholinesterase inhibitors exert less potent effects than required of an ideal anti-dementia agent.…”
Section: Editorialmentioning
confidence: 99%